ASSESSMENT OF TOURISM AND CLIMATE POTENTIAL OF TERRITORIES OF NORTHERN KAZAKHSTAN - Sergey PASHKOV; Gulnur MAZHITOVA; Igor SEDELNIKOV; Gaukhar OSPAN; Yerzhan SAGATBAYEV (Geo Journal of Tourism and Geosites, 2023)
The purpose of the research was to assess the degree of favorableness of the bioclimatic conditions of the territory of Northern Kazakhstan by calculating the tourist climate index (TCI) and analyzing its spatial and temporal variability. Archival, stock materials and data on the main meteorological and climatic indicators for 63 weather stations for the period 1966–2020 were used. The study used methods of mathematical and statistical analysis, GIS technologies. The level of climatic attractiveness varies from "very unfavorable" in the winter months to "comfortable" in the summer. It was determined that the territory of Northern Kazakhstan as a whole is relatively homogeneous in terms of the average annual TCI index (28-38). Depending on the values of the index, 5 categories of climatic attractiveness of the territory of Northern Kazakhstan were identified (comfortable, moderate, neutral, unfavorable, extremely unfavorable). The most favorable conditions for tourist and recreational activities are formed in the summer months in the northeastern and southwestern sectors of the region. Recommendations are given on the spatial placement of tourist and recreational facilities and types of tourist activities in Northern Kazakhstan, taking into account the favorable weather and climatic conditions.